A comparison of physique and physical fitness between different level in Korea elite fencers - Chung, J.-W.; Lee, K.-H. (Exercise Science, 2017)
PURPOSE: The purpose of this study was to investigate the difference between fencers of national team and reserve team on physique and physical fitness. METHODS: Forty six elite fencers participated to this program. The participants were divided into four by gender and level (National Group; NG, Reserve Group; RG). The analysis factors were physique and physical fitness. Independent t-test with SPSS 23.0 was used to analyze the differences between groups. RESULTS: In male fencers, weight (p<.05), %fat (p<.01), BMI (p<.05), chest (p<.001), waist (p<.01), hip (p<.05), upper arm (p<.001), and forearm (p<.01) in physique, back (p<.001) and grip (p<.001) strength, change step jump (p<.001), front & back step (p<.01) in agility, reaction time (p<.001), front (p<.01) and back (p<.05) ankle ROM in flexibility, absolute peak power (p<.01) and relative average power (p<.05) in anaerobic power were significantly high in NG compared to RG. In female, upper leg (p<.05) in physique was significantly high in RG compare to NG whereas back (p<.05) and grip (p<.05) strength, sit up (p<.001) in muscle endurance, change step jump (p<.001), front & back step (p<.01) in agility, reaction time (p<.001), back ankle ROM (p<.05) in flexibility, relative peak power (p<.01) in anaerobic power were significantly high in NG compared to RG. CONCLUSIONS: NG fencers were bigger than RG in male whereas no differences in female and NT has higher physical fitness compare to RG. Thus, there seems to be a strong relationship among physique, physical fitness and performance according to the level and physical fitness training should be conducted to improve performance.